2017
DOI: 10.1177/1056789517737593
|View full text |Cite
|
Sign up to set email alerts
|

Creep crack simulations using continuum damage mechanics and extended finite element method

Abstract: In the present work, elasto-plastic creep crack growth simulations are performed using continuum damage mechanics and extended finite element method. Liu–Murakami creep damage model and explicit time integration scheme are used to evaluate the creep strain and damage variable for various materials at different temperatures. Compact tension and C-shaped tension specimens are selected for the simulation of crack growth analysis. For damage evaluation, both local and nonlocal approaches are employed. The accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Rock, as a heterogeneous natural material, contains a large number of randomly distributed microscopic defects (for instance, cracks, joints, voids), which are the typical manifestations of damage (Pandey et al., 2019). These defects will evolve and develop under the action of external load, resulting in the strength reduction and performance deterioration of rock (Liu et al., 2018).…”
Section: Creep Damage Constitutive Modelmentioning
confidence: 99%
“…Rock, as a heterogeneous natural material, contains a large number of randomly distributed microscopic defects (for instance, cracks, joints, voids), which are the typical manifestations of damage (Pandey et al., 2019). These defects will evolve and develop under the action of external load, resulting in the strength reduction and performance deterioration of rock (Liu et al., 2018).…”
Section: Creep Damage Constitutive Modelmentioning
confidence: 99%
“…According to the creep test results, a series of elasto-viscoplastic creep models have been established under different stress conditions. Many scholars have found that the damage has a great influence on the creep properties of the rocks, and there is a certain coupling relationship between the creep and the damage (Ahmad et al., 2015; Chen et al., 2014; Pandey et al., 2019; Wang et al., 2014b; Yu et al., 2017; Zhang et al., 2014). However, previous studies have mainly focused on the creep behaviors of the intact rocks, and the creep behavior in the rocks with initial damage has drawn little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Chaboche (1988), Hall and Hayhurst (1991), Murakami and Liu (1995), and recently e.g. Pandey et al (2019) used nonlocal continuum models to describe the development of creep damage.…”
Section: Introductionmentioning
confidence: 99%